Do Financing Schemes Affect the Functions of Islamic Banks in Indonesia? - Wahyu Wastuti Suwasdi; Nur Hidayah; Siti Sarah Nasution (Tazkia Islamic Finance and Business Review, 2021)
This study aims to examine the effect of financing schemes on the dual functions of Islamic banks. For intermediary function, its analysis the financing schemes toward profitability. Financing schemes consist of Mudharabah, Qardh, Istisna’ and Ijarah. Meanwhile, the profitability level is measured by Return on Asset (ROA). In this study, the authors used the data from Financial Services Authority (OJK) for the study period from 2014 till 2022. This research used the Multiple Linear Regression to analyze the data. The results of this study indicate that Mudharabah, Qardh, and Ijarah in Full-Fledged  Islamic banks (BUS) are significant effect on ROA. Mudharabah has negative effect but Qardh and Ijarah has positive effect. Meanwhile, in Sharia Business Unit (UUS) Qardh, Istisna’ and Ijarah have significant effect on ROA. All the variables have negative effect. Based on the analysis of Qardh financing, the social function of Islamic banks has not been carried out optimally. Keywords: Mudharabah, Qardh, Istisna’, Ijarah, ROA